Surviving and Thriving With Cancer Using a Web-Based Health Behavior Change Intervention: Randomized Controlled Trial - O'Carroll Bantum, Erin; Albright, Cheryl L; White, Kami K; Berenberg, Jeffrey L; Layi, Gabriela; Ritter, Phillip L; Laurent, Diana; Plant, Katy; Lorig, Kate (JMIR Publications, 2014)
BackgroundGiven the substantial improvements in cancer screening and cancer treatment in the United States, millions of adult cancer survivors live for years following their initial cancer diagnosis and treatment. However, latent side effects can occur and some symptoms can be alleviated or managed effectively via changes in lifestyle behaviors. ObjectiveThe purpose of this study was to test the effectiveness of a six-week Web-based multiple health behavior change program for adult survivors. MethodsParticipants (n=352) were recruited from oncology clinics, a tumor registry, as well as through online mechanisms, such as Facebook and the Association of Cancer Online Resources (ACOR). Cancer survivors were eligible if they had completed their primary cancer treatment from 4 weeks to 5 years before enrollment. Participants were randomly assigned to the Web-based program or a delayed-treatment control condition. ResultsIn total, 303 survivors completed the follow-up survey (six months after completion of the baseline survey) and participants in the Web-based intervention condition had significantly greater reductions in insomnia and greater increases in minutes per week of vigorous exercise and stretching compared to controls. There were no significant changes in fruit and vegetable consumption or other outcomes. ConclusionsThe Web-based intervention impacted insomnia and exercise; however, a majority of the sample met or exceeded national recommendations for health behaviors and were not suffering from depression or fatigue at baseline. Thus, the survivors were very healthy and well-adjusted upon entry and their ability to make substantial health behavior changes may have been limited. Future work is discussed, with emphasis placed on ways in which Web-based interventions can be more specifically analyzed for benefit, such as in regard to social networking. Trial RegistrationClinicaltrials.gov NCT00962494; http://www.clinicaltrials.gov/ct2/show/NCT00962494 (Archived by WebCite at http://www.webcitation.org/6NIv8Dc6Q).